Pengaruh Penyangraian dengan Enerji Gelombang Mikro Terhadap Polifenol dalam Hancuran Keping Biji Kakao - Supriyanto Supriyanto; Haryadi Haryadi; Budi Rahardjo; Djagal Wiseso Marseno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Polyphenols play important roles in taste and flavour development as well as antioxidative property of cocoa products. Chemical changes of the polyphenols occurring during conventional roasting was due to exposure to the oxygen of surrounding air at high temperature(110-200oC) for 20 up to 60 min, depend on the degree of roasting. Shorter time was needed to roast the cocoa nib by using microwave energy. The objective of this research was to investigate changes of polyphenol compounds during microwave roasting of ground cocoa nibs. Deshelled and ground cocoa nib passing through 20 mesh screen was roasted using microwave oven at 20% power for 5 min. Conventional roasting conditions were also adopted for treating the sample using an electric oven at 140 oC for 40 min as comparison. The polyphenols was extracted with acetone 80% and then freez dried. The crude extract was characterized for total polyphenols. Polarity of the polyphenolic fractions was analyzed from the crude extract as well as the ethyl acetate soluble extract by HPLC. Chemical bond of the compounds were detected by Fourier Transform Infrared Spektrophotometer (FTIR). Results indicated that the conventional roasting tend to decrease the polyphenols content while microwave roasting was increase, though the data showed significantly no difference (p≤0,05) . HPLC separation suggested that the roasting of the sample increased in polarity, though FTIR spectra showed similarity in quantity of O-H, C-H, and C=C bonds respectively The microwave oven roasting gave one small additional fraction compared to both sample extracts from the conventional roasted and the unroasted samples which gave two fractions. Further, the ethyl acetate soluble extract from the microwave sample gave eight chromatographic fractions while from those conventional roasted and the unroasted gave two fractions and one fraction, respectively.